2009
DOI: 10.1016/j.yjmcc.2008.10.025
|View full text |Cite
|
Sign up to set email alerts
|

PGC-1α and ERRα target gene downregulation is a signature of the failing human heart

Abstract: Heart failure is a cause of significant morbidity and mortality in developed nations, and results from a complex interplay between genetic and environmental factors. To discover gene regulatory networks underlying heart failure, we analyzed DNA microarray data based on left ventricular freewall myocardium from 59 failing (32 ischemic cardiomyopathy, 27 idiopathic dilated cardiomyopathy) and 33 non-failing explanted human hearts from the Cardiogenomics Consortium. In particular, we sought to investigate cardiac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
129
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(145 citation statements)
references
References 83 publications
7
129
1
2
Order By: Relevance
“…Indeed, Ppargc1a/b-knockout mice have reduced cardiolipin and impaired mitochondrial respiration. Third, a number of studies in animal models and in humans have shown reduced levels of PGC-1α and ERR transcripts and protein levels in heart failure (117)(118)(119)(120)(121). Collectively, these data clearly connect diminished mitochondrial respiration capacity with reduced ERR/PGC-1 signaling and suggest that this may be a final common pathway in heart failure ( Figure 3).…”
Section: Energy Metabolic Derangements In the Failing Heartmentioning
confidence: 85%
“…Indeed, Ppargc1a/b-knockout mice have reduced cardiolipin and impaired mitochondrial respiration. Third, a number of studies in animal models and in humans have shown reduced levels of PGC-1α and ERR transcripts and protein levels in heart failure (117)(118)(119)(120)(121). Collectively, these data clearly connect diminished mitochondrial respiration capacity with reduced ERR/PGC-1 signaling and suggest that this may be a final common pathway in heart failure ( Figure 3).…”
Section: Energy Metabolic Derangements In the Failing Heartmentioning
confidence: 85%
“…The PGC-1 coactivators have also been implicated in human disease. For example, the expression and activity of PGC-1␣ has been shown to be reduced in heart failure and diabetes (15,16).…”
mentioning
confidence: 99%
“…In samples taken from explanted hearts, during transplantation in patients with advanced heart failure, the level of the enzymes of FAO was low compared to the non-failing hearts [218]. The reduction of mitochondrial biogenesis and of FFA oxidation in the advanced phase of CHF is, as already seen, caused by the reactivation of the fetal gene program through the upregulation of HIF-1 and the downregulation of PPAR, \ERR, of SIRT1 and of the PGC-1network demonstrated in myocardial samples of patients with end-stage heart failure compared with explanted non failing hearts [219]. The expression of these transcription factors and coactivators is reduced in pathological hypertrophy and heart failure whereas it is upregulated in physiological forms of hypertrophy related to postnatal growth or exercise training [220] so furnishing a precise boundary between physiologic and pathologic cardiac growth.…”
Section: Metabolic Dysfunction In Chronic Heart Failurementioning
confidence: 65%